ZnO Nanowall Networks for Sensor Devices: From Hydrothermal Synthesis to Device Demonstration. (1st January 2018) - Feng, Zixuan; Rafique, Subrina; Cai, Yi; Han, Lu; Huang, Ming-Chun; Zhao, Hongping
Abstract : This paper reports the synthesis of ZnO nanowalls (NWLs) on various substrates by low cost and scalable hydrothermal approach targeting for flexible sensor device applications. Prototype flexible piezoelectric sensor devices using the synthesized ZnO NWLs were demonstrated through a transfer process. The roles of precursor chemical concentration and aluminum seed layer thickness in determining the morphology and the growth rate of the as grown ZnO NWLs were investigated. Effects of thermal annealing on the morphology and the crystalline quality of the NWLs were studied. To fabricate the sensor devices, ZnO NWL layers were transferred on to different substrates using thin Polymethyl methacrylate (PMMA) layer. Wafer scale transfer of thermally annealed ZnO NWLs to flexible substrates has been achieved. The demonstrated prototype devices can generate up to 300 mV of output voltage with external applied forces. Simulation model using COMSOL Multiphysics was developed to study the piezoelectric properties of the ZnO NWLs based devices. The simulation results agree well with the experimental data. The demonstrated ZnO NWLs based flexible devices are applicable for wearable nanodevices and motion sensors that will benefit from their large surface areas.